2021
DOI: 10.1111/acv.12715
|View full text |Cite
|
Sign up to set email alerts
|

Testing branding techniques on species common names to improve their fundraising profile for conservation

Abstract: In the search for new ways to bring attention to the conservation of neglected species, marketing is increasingly recognised as offering new insights. Brand creation frameworks provide guidelines to create names or symbols for products that will differentiate them from the competition. In this paper, we examine if species common names that follow these guidelines can improve their fundraising potential. Using a novel choice experiment format that employs a budget allocation task, we evaluate if species common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Therefore, perhaps public consumption and recreational behavior has more impact than naming on fish species’ Wikipedia attention. Overall, our results support suggestions that conservation marketing techniques (here, naming) can particularly affect species that are typically less popular than others (Díaz‐Restrepo et al., 2022; Veríssimo et al., 2017). Moreover, they add to the notion that celebrities can help generate public attention (Anderson, 2013; Goodman & Littler, 2013), especially for less recognized brands (i.e., species [Udo & Stella, 2015]).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, perhaps public consumption and recreational behavior has more impact than naming on fish species’ Wikipedia attention. Overall, our results support suggestions that conservation marketing techniques (here, naming) can particularly affect species that are typically less popular than others (Díaz‐Restrepo et al., 2022; Veríssimo et al., 2017). Moreover, they add to the notion that celebrities can help generate public attention (Anderson, 2013; Goodman & Littler, 2013), especially for less recognized brands (i.e., species [Udo & Stella, 2015]).…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, even though Díaz‐Restrepo et al. (2022) and Blades (2020) found that species names do not significantly influence conservation support for them, they focused on mammals (whose favorable aesthetics may have overshadowed any influence of naming). Thus, it should be explored whether the potential impacts of naming remain insignificant across other taxonomic groups.…”
Section: Introductionmentioning
confidence: 99%
“…R. Soc. B 290: 20231970 common names can affect opinions about conservation worth [82]; but see [83,84]).…”
Section: (B) Scientific Naming and Public Attention To Sciencementioning
confidence: 99%
“…2020; Díaz‐Restrepo et al . 2022), the possession of a name seems to be important for the effectiveness of flagship individuals. For example, Cecil the lion's popularity has been partly attributed to use of his personal name instead of his research code number (MAGM1) in marketing (Macdonald et al .…”
Section: The Concept and Characteristics Of Flagship Individualsmentioning
confidence: 99%
“…The assigned name allows flagship individuals to become recognized, be referred to as unique individuals, and be attributed a status not unlike personhood (Levin 2015). Although links between the common name of a species and the success of conservation efforts remain unclear (eg Carvell et al 1998;Gregg et al 2020;Díaz-Restrepo et al 2022), the possession of a name seems to be important for the effectiveness of flagship individuals. For example, Cecil the lion's popularity has been partly attributed to use of…”
mentioning
confidence: 99%